Curua-Una: 50 anos de Pesquisa - Pokorny, B.; Vasconselos, L. (Faculdade de Ciencias Agrarias do Para (FCAP), 2002)
The Experimental Station of Curuá-Una is a milestone for tropical silviculture of the Brazilian Amazon. Here started intensive scientific research about the Amazonian forests in Brazil. Since nearly 50 years, generations of researchers related to forest science, used Curuá-Una for experiments and to increase the understanding about the ecosystem and the impacts of forest management on the vegetation. When we heard about the plan to close Curuá-Una, we thought to document all these studies and generated knowledge in a CD. To identify all what has been produced, we started to research in public and private libraries and established contacts to numerous researchers. We identified 64 works, published and not published, from 29 authors, showing a wide variety of topics mostly related to aspects of forest science. To document and disseminate this diverse knowledge, we produced this CD-ROM, not considering questions of quality or scientific relevance.To facilitate working with the CD-ROM, we established keywords and author’s indices as well as other useful tools. Thus the lector will find a lot of useful information about forestry in the Amazon. However, the CD-ROM will also reveal one of the most critical deficiencies of scientific work in the Amazon: the lack of continuity caused by a lack of resources, changing staff, lost of data, natural events, invasions etc. After studying this work, it will be easily to imagine the immense value of the described experiments, if they would have been systematically continued. Thus, we hope that this CD-ROM may contribute to continuous scientific research in Curuá-Una.